What’s So Special About Medically Assisted Dying? - Sumner, Wayne (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
Critics of Canada’s current medical assistance in dying (MAiD) regime commonly employ two types of argument: 1) that the number of annual provisions shows that it is out of control or on a slippery slope, and 2) that it puts persons with disabilities at risk. Both arguments commit the same fundamental mistake: treating MAiD as different in kind from other forms of medical treatment, including end-of-life treatment.